Answer:
i think that the answers is -16x + 5
Answer:
x=-3
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
3(x−6)+6=5x−6
(3)(x)+(3)(−6)+6=5x+−6(Distribute)
3x+−18+6=5x+−6
(3x)+(−18+6)=5x−6(Combine Like Terms)
3x+−12=5x−6
3x−12=5x−6
Step 2: Subtract 5x from both sides.
3x−12−5x=5x−6−5x
−2x−12=−6
Step 3: Add 12 to both sides.
−2x−12+12=−6+12
−2x=6
Step 4: Divide both sides by -2.
−2x
−2
=
6
−2
x=−3
Answer:
4<x<6
Step-by-step explanation:
4 is smaller than x
and x is samller than 6
so its 5
About 3.40 rounded to the tenths place
Answer:
For the shape you must do 3*3*3 + 2*2*2 + 1 unit cubed, or 36 units^3
For Jessy's jewelry box, you must multiply the side lengths, 3*10*3, or 90 inches^3